Single p-block atom doped boron nitride monolayer: versatile catalysts for nitrate reduction beyond transition metals - Md Tarikal Nasir; Qingchao Fang; Hanqing Yin; Dimuthu Wijethunge; Xiuwen Zhou; Anthony P O’Mullane; Aijun Du (JPhys Materials)
Electrochemical reduction of nitrate ( ${\text{NO}}_3^ - $ ) to ammonia is a sustainable strategy to convert the pollutant nitrate into high-valued chemicals. Currently, the nitrate reduction reaction (NO _3 RR) is mainly based on transition metal catalysts. Here, by using density functional theory calculations, we studied six p -block atoms doped in 2D boron nitride (BN) monolayers for the NO _3 RR. Our results reveal that the doped BN monolayers are thermodynamically stable, and that ${\text{NO}}_3^ - $ can be strongly absorbed and activated on the In@BN, Si@BN, Ge@BN and Sn@BN monolayers. BN is a promising substrate support for catalysts due to high stability and thermal resistance. Among the six doped BN monolayers, In@BN and Sn@BN exhibit exceptional NO _3 RR performance with a limiting potential of only −0.30 V. Additionally, the hydrogen evolution reaction can be completely suppressed due to the weak adsorption of protons on the catalyst surfaces. Our work provides a new avenue on designing p -block atom-based catalyst’s for efficient NO _3 RR.